2020
DOI: 10.1080/02673843.2020.1716817
|View full text |Cite
|
Sign up to set email alerts
|

A novel way to engage youth in research: evaluation of a participatory health research project by the international children’s advisory network youth council

Abstract: Background: Little is known about the impact of a participatory approach in adolescent health research and the specific benefits youth derive from such experiences. This study evaluates the benefits and limitations of involving young patients as co-researchers in the creation and execution of an international participatory health research project. Methods: Standardized feedback surveys and qualitative interviews were employed to evaluate the impact of coresearchers' personal and academic growth. Participation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 26 publications
(30 reference statements)
0
15
0
Order By: Relevance
“…Furthermore, studies that involved a youth-led component reported improvements in capacity building markers of empowerment and influence, enhanced confidence, and gave adolescents a voice in research that concerns their lives. The use of YAGs exemplifies a novel ( 181 ) yet practical and effective strategy to meaningfully engage adolescents in an adolescent-led approach throughout the entirety of the research cycle ( 114 , 130 ). Similarly, in a recent scoping review investigating the use of YAGs in health research, Sellars et al determined that YAGs are a valuable yet underutilized method of involving young people in effective research development and translation globally ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies that involved a youth-led component reported improvements in capacity building markers of empowerment and influence, enhanced confidence, and gave adolescents a voice in research that concerns their lives. The use of YAGs exemplifies a novel ( 181 ) yet practical and effective strategy to meaningfully engage adolescents in an adolescent-led approach throughout the entirety of the research cycle ( 114 , 130 ). Similarly, in a recent scoping review investigating the use of YAGs in health research, Sellars et al determined that YAGs are a valuable yet underutilized method of involving young people in effective research development and translation globally ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study published by the same team captured the details of this approach in detail. 13 Second, additional data were collected through 15 semistructured, standardized interviews of adolescent medicine physicians across Canada and the United States. Third, perspectives of AYA patients and their caregivers were gathered independently using a 20-item survey.…”
Section: Methodsmentioning
confidence: 99%
“…Third, this study directly includes youth as coresearchers (YCR) from the creation of research objectives and implementation to data evaluation and knowledge translation. 13 The involvement of patients as coresearchers is a relatively novel concept and one that is not adequately studied in literature. Although researchers agree that youth involvement is beneficial for all stakeholders involved, the process taken to facilitate tangible partnerships with youth advisors remains unclear.…”
mentioning
confidence: 99%
“…We held two workshops entitled 'Choosing meaningful outcomes for research: making sure young people have their say' at the international iCAN Summit in Edinburgh, UK, on 12th July 2018. iCAN is an international consortium of youth advisory groups established in 2015. The consortium aims to provide a way for the perspectives of young patients to inform the decision-making processes of regulatory agencies and pharmaceutical companies in the development of clinical trials and treatments, and to facilitate researchers and clinicians in consulting with CYP when designing studies [21]. iCAN comprises 21 youth patient advisory groups (YPAGs) with members aged 8-25 who are patients at local research institutions and hospitals or have links to these.…”
Section: Main Textmentioning
confidence: 99%